FROM THE EXPERIENCE OF IMPLEMENTATION OF THE EDUCATIONAL AND SCIENTIFIC PROGRAM “PROFESSIONAL EDUCATION” FOR RECIPIENTS OF THE THIRD (EDUCATIONAL AND SCIENTIFIC) LEVEL OF HIGHER EDUCATION IN SPECIALTY 015 “VOCATIONAL EDUCATION” (BY SPECIALIZATIONS) - Nataliia P. Volkova; Olha V. Lebid (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article reveals the experience of implementing the educational and scientific program “Professional Education” for applicants of the third (educational and scientific) level of higher education specialty 015 Professional Education (by specializations) at Alfred Nobel University. Features and purpose of the educational and scientific program “Professional Education”, as well as its structure (educational and scientific components) are described. The volume of the educational component of the educational and scientific program is given – 45 ECTS credits, of which the cycle of general (18 ECTS credits) and professional (27 ECTS credits) training, including the discipline of free choice of applicants (12.5 ECTS credits). Particular attention in the educational and scientific program is paid to the content of competencies sufficient to solve complex problems in the field of professional and / or research and innovation in the field of education. A brief description of the content of the scientific component of the program, which provides for the implementation of their own basic and / or applied research with the appropriate design of the obtained scientific results in the form of a dissertation, testing of research results. Methodological approaches (systemic, competence, activity, andragogic, student-centered, personality-oriented, participatory, environmental, integrative) and principles (systematization, scientificity, systematicity and consistency, clarity, integration of theory and practice, consciousness and activity) are substantiated and defined. Independence and activity of subjects in training, interdisciplinary connections, a positive emotional background of training, maintenance of unity of educational, developmental and educational functions are put into practice in the educational and scientific program. The main types of classes, methods and means of teaching future doctors of philosophy are identified. Emphasis is placed on the peculiarities of graduate research activities of graduate students. Ways of realization of individual educational trajectory for each postgraduate student are demonstrated (drawing up of the individual curriculum; a choice of the block of disciplines from a selective component at one’s own will, choosing the subjects of scientific and practical research works according to the interests of applicants of higher education; the organization of independent work of applicants by means of educational computer programs and electronic textbooks; certification courses for the formation of additional professional competencies; distance education; drawing up an individual schedule of graduate students; types of communication between research and teaching staff with applicants; participation in various extracurricular activities). Emphasis is placed on the scientific achievements of higher education seekers (publications in professional journals, collections of scientific papers, reporting the results at annual scientific and practical conferences, publication of research results in a foreign language in periodicals, participation in the research work of the Department of Innovation Technologies in Pedagogy, Psychology and Social Work, scientific and pedagogical internship, etc.).